Comparisons of urban and rural heat stress conditions in a hot–humid tropical city - Ahmed A. Balogun; Ifeoluwa A. Balogun; Zachariah D. Adeyewa (Taylor & Francis Group, 2010)
Background: In recent years the developing world, much of which is located in the tropical countries, has seen dramatic growth of its urban population associated with serious degradation of environmental quality. Climate change is producing major impacts including increasing temperatures in these countries that are considered to be most vulnerable to the impact of climate change due to inadequate public health infrastructure and low income status. However, relevant information and data for informed decision making on human health and comfort are lacking in these countries. Objective: The aim of this paper is to study and compare heat stress conditions in an urban (city centre) and rural (airport) environments in Akure, a medium-sized tropical city in south-western Nigeria during the dry harmattan season (January–March) of 2009. Materials and methods: We analysed heat stress conditions in terms of the mean hourly values of the thermohygrometric index (THI), defined by simultaneous in situ air temperature and relative humidity measurements at both sites. Results: The urban heat island (UHI) exists in Akure as the city centre is warmer than the rural airport throughout the day. However, the maximum UHI intensity occurs at night between 1900 and 2200 hours local time. Hot conditions were predominant at both sites, comfortable conditions were only experienced in the morning and evenings of January at both sites, but the rural area has more pleasant morning and evenings and less of very hot and torrid conditions. January has the lowest frequency of hot and torrid conditions at both sites, while March and February has the highest at the city centre and the airport, respectively. The higher frequencies of high temperatures in the city centre suggest a significant heat stress and health risk in this hot humid environment of Akure. Conclusions: More research is needed to achieve better understanding of the seasonal variation of indoor and outdoor heat stress and factors interacting with it in order to improve the health, safety, and productivity of Akure city dwellers.